A2_2 Nanoparticle Hyperthermia Heat Transfer - Forster, James; Bryan, Mark; Stone, Alex (Physics Special Topics, 2012)
This paper attempts to model the heating of a tumour by superparamagnetic iron oxide nanoparticles of diameter 15nm in an alternating 1T magnetic eld. It was calculated that in such a field alternating at the maximum angular frequency of the particles that the required 2.5K rise in temperature required for cell death could be achieved in 10 minutes using a minimum number of nanoparticles in the order of 108, assuming that all nanoparticles injected reached the target cells and that all of the heat was transfered to the tumour.